Analysis of Post Mortem Findings in Suicidal Hanging- Study in a Tertiary Care Hospital - Jabin, Nashat; Moinuddin, KM; Sultana, Parveen; Rahman, Md Ridwanur; Reza, AM Selim (Journal of Shaheed Suhrawardy Medical College, 2022)
Background: Suicide is the act of intentionally taking your own life. Hanging is always suicidal unless otherwise proved. It is a from of violent asphyxial death. It produces painless death for the victims so that it is a widely practiced method of suicide. Every year, 8 lac people die for hanging. In Bangladesh hanging in one of the Commonest methods of suicide. Objectives: The objective of this study was to find out Socio-demographic characterizes of victims, common ligature materials used by victims and post mortem findings. Materials and method: A retrospective cross sectional study was done in Shaheed Suhrawardy Medical College mortuary during the period of July 2018 to December 2020. During this period data were collected from 1815 cases of medico legal autopsies by purposive sampling. Results: A total of 1815 medico legal autopsies were analysed of which 818 (45.06%) were deaths due to hanging. out of these 818 cases maximum 395(48.28%) deaths due to hanging were in age group of 21-30 years. Majority of the cases 546(66.74%) were observed in female and others in male 272(33.25%). Majority 425 (51.95%) of victims had used Dopatta (Orna) as a ligature material. Cyanosis of finger tips and nail beds was the commonest 797 (97.43%) finding in cases of asphyxia death due to hanging. Conclusion: In this study all the cases of hanging were suicidal and no case of post-mortem hanging was documented. Majority of the victims were between 21-30 of age (48.28%). Twothirds of them were females. Most frequent occupation was students. More than two thirds belonged to low socio-economic condition and none of the case were from higher socio-economic condition. More than 70% victims were found inside house with locked door. In more than threefourth of the cases, the ligature material was dopatta (orna), apparently because of cost and availability. In most cases the point of suspension was ceiling fan. Complete hanging was most frequent type of hanging. Other external and internal autopsy findings were like book picture. J Shaheed Suhrawardy Med Coll 2021; 13(1): 36-40